2016
DOI: 10.1186/s40662-016-0065-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of combined versus separate carbachol and brimonidine drops in correcting presbyopia

Abstract: BackgroundTo test and compare in a masked fashion the efficacy of using a parasympathomimetic drug (3% carbachol) and an alpha-2 agonist (0.2% brimonidine) in both combined and separate forms to create optically beneficial miosis to pharmacologically improve vision in presbyopia.MethodsA prospective, double-masked, randomized, controlled clinical trial was conducted. Ten naturally emmetropic and presbyopic subjects between 42 and 58 years old with uncorrected distance visual acuity of at least 20/20 in both ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Pharmaceutical treatments for presbyopia include stimulating the contraction of the ciliary muscles in the presence of different miotics(Abdelkader, 2015;Abdelkader and Kaufman, …”
mentioning
confidence: 99%
“…Pharmaceutical treatments for presbyopia include stimulating the contraction of the ciliary muscles in the presence of different miotics(Abdelkader, 2015;Abdelkader and Kaufman, …”
mentioning
confidence: 99%
“…The UNVA was measured with the Jaeger scale, and all the treated subjects abandoned the use of near glasses. He also compared the monocular instillation of 3% carbachol and 0.2% brimonidine in combined and separate forms, demonstrating a significant improvement in mean near visual acuity in the combined solution group [7]. Benozzi et al [10] reported that 100% of patients achieved near vision of J1 after the topical instillation of pilocarpine 1% and 0.1% diclofenac.…”
Section: Discussionmentioning
confidence: 99%
“…Accommodation can be pharmacologically stimulated by the contraction of the ciliary muscle. Some topical treatments have been studied [6][7][8][9][10], reporting an improvement in near vision with the topical application of muscarinic cholinergic agonists. We previously reported our results with a new pharmacological therapy (FOV tears) for presbyopia [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…On the 1 hand, brimonidine, an α2-receptor agonist used in glaucoma, induces pupillary action, producing significant miosis, mainly under low light conditions [48]. Brimonidine binds to receptors on the presynaptic nerve endings of the dilator muscle and obstructs further release of the neurotransmitter into the synaptic cleft, thus reducing the activity of the dilator muscle, generating a more miotic pupil [37]. In contrast, carbachol, unlike pilocarpine, is a full parasympathomimetic agent that stimulates the muscarinic and nicotinic receptors on the iris sphincter muscle to produce miosis, increase the depth-of-focus [34], and promote acetylcholine release from parasympathetic nerve endings.…”
Section: Pinhole Effectmentioning
confidence: 99%